Students’ Satisfaction with the Quality of their Studies and the Loyalty in Department of Management Science and Technology of the International Hellenic University (Kavala University Campus) - Tsairidis, Charalampos; Gatidou, Despoina (Advances in Social Sciences Research Journal, 2023)
The purpose of this study is to investigate the level of students’ satisfaction of their departments by the use of factors which are absolutely related to educational and supporting process during their studies. Moreover, it tries to connect the degree of student satisfaction with their loyalty to the Foundation, in order to assess the possibility to continue their studies at a higher level (master degree, doctoral).